AN ANALYSIS OF THE CONCEPT OF INJUNCTION AS A REMEDY IN THE NIGERIAN LEGAL SYSTEM - Nnenna Oteh, Anita (CENTRAL ASIA AND THE CAUCASUS, 2024)
It is clear manifestation that the law and practice of the equitable remedy of injunction occupied a very important terrain or place in the legal system of Nigeria. This is because besides, the fact that it transcends both the substance and adjectives or procedural laws, its ' impact as a strong and effective weapon in the practice of the law cannot tie over emphasized, most especially since it cuts across all branches of laws via constitutional and administrative laws, the laws of contract, tort and banking, the laws relating to, and the conduct of election in Nigeria etc. in this regard, one cannot easily forget the activities of the A.B.N. (Association for Better Nigeria). In the cases of ABIMBOLA DAVIES VS the national electoral COMMISSION (NEC) spear headed by Francis Arthur Nzenbe during the aborted third Republic in Nigeria in 1993. It can therefore be suggested quite rightly from the above that the reason for the choice of this topic is because of the pervasiveness of the aw and practice of injunction in all its ramification of ouj, law and the purpose of course is to analyze how consistent, effective and purposeful our courts and legal practitioners have granted the principle of injunction and its ultimate effect on our legal system and our society at large. This project is divided into five chapters in all. Chapter one is devoted wholly to indu introductory details, that is definition origin and "exception of legal principles of injunction. Next comes chapter two, which will contain the types of and scope 2f injunction in particular situation Next is chapter three, which deals with the application and effect of junction in Nigeria. In other words, this chapter deals with the practice and procedure of the law of injunction. In this regards, this chapter touches the mode of applying for injunction,-relevant civil procedure rule, the principle guiding the grant and the effect of injunction. The fourth chapter takes a clinical and analytical work at the topic: self. It touches on the delay and abuse of the principles of injunction Advantages and Disadvantages) and when injunction will be refused. The last which is chapter five, deals with conclusion of this work. It proffers suggestion by orders of injunction can be reduced d the beeriest minimum if not out rightly eliminated.